Growth Characteristics and Yield of Local Chili Peper 2 cultivars - BRIATIA, Xoxiong; KEOCHAMPHONE , Somkid; LORCHAMYEU, Chanthavong (Souphanouvong University Journal Multidisciplinary Research and Development, 2019)
This experiment was to observe plant growth characteristics and yield of local chili peper 2 cultivars. The experimental design was CRD with 3 replications and 2 treatments (Cultivar No.1, small-short fruits “14 x 0.03 mm” and Cultivar No.2, big-long fruits “42 x 0.05 mm”), planted 1 plant/hole with distance of 50 x 50 cm and the seedling ages was 1 month’s old (3-4 of true leaves). Results found that local chili peper cultivar No.2 showed plant high better than cultivar No.1 when the age increases such as the flowering stage (120 days of age) the plant high was 46.20 cm and the pre-harvest stage (180 days of age) was 91.40 cm height. On the other hand, seedling survival rates of the 2 cultivars were higher than 80%. The number of branches, fruit sizes and weight, number of seed per fruits and total yield per plant found that in the flowering stages of 2 cultivars showed number of branch 4-6 branches/plant, while at pre-harvest stages found cultivar No.2 shown 19 branches/plant and more than cultivar No.1 (14.4 bracnes/plant). Likewise, the cultivar No.2 showed the fruit sizes 4.64 x 0.05 cm, fruits weight 0.91 g/fruit and number of seeds 33.75 seeds/fruit, respectively, higher than that cultivar No.1 (1.51 x 0.03 cm fruit sizes, 0.23 g/fruit and 14.75 seeds/fruit). Moreover, total yield of fresh fruits was showed 95.5 g/plant with cultivar No.2 and higher than cultivar No.1 (82.33 g/plant). Generally, indicated that local chili peper cultivar No.2 shown plant growth characteristics, number of branches, fruit sizes and weight, number of seed per fruits higher than that cultivar No.1, respectively. However, the 2 cultivars of local chili peper stilled importance and necessary to support for fammers growth and conservation in further.